The Structural Analysis of Pan’s Labyrinth by Guillermo Del Toro as A Fantastic Film - Ayuningtyas, Paramita (Humaniora, 2015)
Using structural approach and Tzvetan Todorov?s theory about ?absolute hesitation?, this research discusses how the narrative and cinematographic elements build Pan?s Labyrinth (2006) as a unique fantastic film. Directed by Guillermo del Toro Pan?s Labyrinth is a film in Spanish about a little girl named Ofelia who has to live in a house in the middle of the forest and experiences many bizarre incidents, including meeting the Faun. The narrative elements discussed in this paper are motives and themes, while the cinematographic elements are settings, lighting and colours. To analyze the data, this research uses a qualitative method that lies on library research. The result of the discussion shows how the intrinsic elements successfully built ?absolute hesitation? in Pan?s Labyrinth. Thus, Pan?s Labyrinth can be categorized as a fantastic film with a dark twist that is Del Toro?s irreplaceable characteristic in directing films.